The Impact of Administrative Staff's Role on the Effectiveness of SIMRS in Recording the Daily Census of JPPK Patients at Hospital X - Rosmiyanti Devi, Neng Sri; Susanti, Ai Susi (Asian Journal of Environmental Research, 2025)
This study analyzes the role of administrative staff in enhancing the effectiveness of the Hospital Management Information System (SIMRS) in recording the daily census of patients under the Health Service Guarantee (JPPK) at Hospital X. Employing a case study design with qualitative and quantitative methods, data were collected through observations and document analysis of census reports from January to March 2025. Results indicate a significant correlation between the accuracy, competence, and compliance of administrative staff and the effectiveness of SIMRS. An error rate of 2.96% was found, primarily caused by inaccurate input of consulting doctor data, medical procedures, and medication details. Medication changes were often due to stock limitations, requiring substitutions and approval from patients, which in turn demanded timely adjustments by staff. Errors in medication pricing occurred due to delays in updating price information in the SIMRS system. These issues point to a broader problem of limited coordination and delayed information flow between hospital units. The findings underscore the importance of administrative staff with adequate knowledge and skills in using SIMRS. Their performance significantly impacts the accuracy and efficiency of JPPK patient census recording, highlighting their strategic role in supporting integrated hospital information systems.